The Effect of Organizational Commitment and Competence on Work Motivation and Work Performance at SMA Negeri Tapung District - Ahmad Rafa'i; Achmad Tavip Junaedi; Nyoto; Nicholas Renaldo; Fazal Mohamed Mohamed Sultan (First Ciera Publisher, 2023)
The purpose of this study was to determine the effect of Organizational Commitment, Competence, on the motivation and performance of teachers in SMA in Tapung District. The method used in collecting data in this research is a questionnaire. The population in this study were all teachers at SMA Negeri in Tapung sub-district with a total of 112 teachers. The sample of this study used the Stratified Random Sampling method with Structural Equation Modeling (SEM) PLS 3.0 analysis. The results showed that Organizational Commitment had a positive and insignificant effect on Motivation, Competence had a positive and insignificant effect on Performance, and Organizational Commitment had a positive and insignificant effect on motivation. on performance, competence has a positive and significant effect on performance, motivation has a positive and insignificant effect on performance in high school teachers in Tapung District.